2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626465
|View full text |Cite
|
Sign up to set email alerts
|

Internal validation of a telemedical system for monitoring patients with chronic respiratory diseases

Abstract: One of the most promising and innovative developments in medicine are telemedical systems. The system PulmoTel 2010 and its internal validation are presented, focusing on the system architecture, hardware, software and communication solutions. PulmoTel 2010 consists of a distant server managing users and medical devices, as well as data transmission, processing, storage and presentation. The server cooperates with home units used by patients, capable of performing lung function tests. All the elements communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Implementation of the EIT in the MIM was preceded by comprehensive simulation studies [8], [9], [12]- [16] and by the designing of an appropriate hardware configuration [17], [18], [20]. This stage can be thought of as a feasibility study, and wide clinical tests have been planned.…”
Section: Eitmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of the EIT in the MIM was preceded by comprehensive simulation studies [8], [9], [12]- [16] and by the designing of an appropriate hardware configuration [17], [18], [20]. This stage can be thought of as a feasibility study, and wide clinical tests have been planned.…”
Section: Eitmentioning
confidence: 99%
“…For this reason, the MIM is adapted to perform a single or multiple airflow interruption using a shutter valve operating at the mouth and to collect the postocclusion data in a temporal memory buffer (up to several hundreds of tests) or send them directly to the central medical server. Detailed hardware and software solutions, applied in every layer of the telemedical system, and the resulting functionalities were outlined in [17] and [18].…”
Section: A System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…This application exactly mimics the operation of a HU: it assumes a specific serial number, accepts configuration files from the server, enables the selection of a given patient from the list and the date from the unrolled calendar, can set the ambient pressure, and finally generate spirometric or interrupter data. Both tests are simulated using computational models for the respiratory system [36,37]. Generated data are randomized by a rescaling procedure, with parameters depending on the date of simulated examination, allowing the trend visualization of calculated indices.…”
Section: Tests Of System Softwarementioning
confidence: 99%
“…The system mentioned in that application has been used for management of patients with asthma, COPD, hypertension, inflammatory bowel disease, and multiple sclerosis. Jablonski (Jablonski, et al 2010) reported a system that monitors the patient health at home, and sends the collected data to a remote server via internet Virtual Private Network (OpenVPN) using the HTTP protocol. The telemedical system therein described is dedicated to patients needing a long term monitoring of their lung function.…”
mentioning
confidence: 99%